Vocational skill training programs for persons with intellectual disability (PID) and trainers' perspective during and post vocational skill training - Kundurthi Venkatesh; Shanivaram K Reddy; Hareesh Angothu (Journal of Family Medicine and Primary Care)
Background: Employment is one of the primary goals of persons with intellectual disabilities (PID). Employment can lead to positive psychosocial and economic benefits for people with ID, but people with disabilities are not afforded this opportunity to contribute to society through work due to multiple challenges, as well as the transition from vocational skill training to getting employed for PID is more challenging. Materials and Methods: Seven vocational skill trainers were chosen from the seven vocational skill training centres offering skill training for PID and located in urban Bengaluru were selected using a purposive sampling design for this study. The trainers were interviewed to understand their perspectives on challenges during and post vocational training for PID. Results: Training offered to PID in several vocational centres ranged from unskilled to semi-skilled. A range of barriers including gaps in awareness and knowledge of the various training programs for PID challenges associated with their transition after training, unique challenges in placing the trained PID into external organizations, stigma, and attitudinal barriers associated with disability are described to be influencing the skill training of PID and their subsequent employment. Conclusion: Skill training offered for PID across the centres with significant challenges while providing the training and supporting their transition into the community for employment. The challenges of the PID need to be studied at a broader level through including all the stakeholders.